Pembelajaran Saintifik Dan Kemampuan Berpikir Kritis Anak Usia Dini - Yardi Haninuna; Tirsa Elik; Aguinda Missa; Irma Nubatonis; Ledi Bulla; Esi Soe; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Early childhood education is a crucial stage for developing critical thinking abilities as a 21st century skill. The aim of this research is to determine the influence of scientific learning on the critical thinking abilities of children aged 5-6 years. The method in this research is quantitative with an ex-post facto approach. The sampling technique used total sampling, namely 15 children aged 5-6 years at PAUD Senam Binlaka, Kupang City. Data collection techniques use scientific learning questionnaires and assessment rubrics for critical thinking. The data analysis technique is simple linear regression with SPSS 26.0. The results of these findings show that scientific learning has a positive and significant effect on the critical thinking abilities of children aged 5-6 years, amounting to 34.7, which means that the better the application of scientific learning, the greater the critical thinking abilities of young children. It is hoped that PAUD teachers will implement scientific learning optimally through the stages of observing, asking, trying, reasoning and communicating, as well as involving parents to support the development of children's critical thinking.